Lo que cura es el vínculo - Barbieri, Alejandro De (Miscelánea Comillas, 2005)
The bond is what heals. This fundamental concept proposed by Irvin D. Yalom in his book «Existential Psychtherapy» is an idea that is still in effect. The bond. The relationship. The techniques aren’t as important. If technique should come first, we’ll be giving less importance to the individual. If a real bond is created with the person in need, the technique will come, but it’s never a priority. The psychologists use all the arguments to bring down the myth of the tests. But this doesn’t happen so often. In most of cases the patient waits for the result of the test with such an anxiety, that make us think of those who are waiting for the fortuneteller’s predictions. Prof. Frankl said: «Life’s not a Rorschach’s test, but an enigma. What I call will to meaning goes far beyond the simple perception of a graphic». The encounter sets you free, love sets you free, these values display a whole new world of possibilities to the patient. In the end it is not the psychologist or the technique who heals the patient. What really helps him is the encounter between two persons, one willing to help and the other to be helped.